Electronic Governance and Open Society : Challenges in Eurasia : 6th International Conference, EGOSE 2019, St. Petersburg, Russia, November 13–14, 2019, Proceedings /: Challenges in Eurasia : 6th International Conference, EGOSE 2019, St. Petersburg, Russia, November 13–14, 2019, Proceedings. (2020) - Unknown
No abstract available